Competitiveness framework to support regional-level decision-making in the wine industry: A systematic literature review - Jorge Mota; Rui Costa; António Moreira; Silvana Serr\~ao; Carlos Costa (Wine Economics and Policy, 2021)
This study aims to identify the main performance indicators and group them in dimensions within a regional competitiveness framework to support decision-making in the wine industry. For this research, a systematic literature review (SLR) was conducted in the Scopus database. There is a limited number of studies identifying indicators with impact on the performance of wine regions, and even fewer studies including indicators in an integrated approach to measure the different dimensions of wine regions' performance. From a set of 85 papers, only 9 studies related to performance indicators with a specific focus on the regional level were considered. We document that under a convention framework, economic and territorial indicators cover 84.90% of all SLR indicators analysed, and under a regional competitiveness framework, infrastructure and innovation and intellectual capital indicators fill 81.25% of all the indicators. As this group of indicators is limited to a set of sub-dimensions, we found that several groups of indicators are misrepresented, such as the ones related to human and socio-cultural capital areas, which play a crucial role in the regional competitiveness of the wine industry. This paper contributes to the literature identifying indicators according to convention and regional competitiveness frameworks in three dimensions - economic, environmental and territorial dimensions and five main areas - productive capital, human capital, socio-cultural capital, infrastructure and intellectual capital. These indicators are to be used at regional-level to support decision-making in the wine industry. For regional entities, it discloses the most pertinent indicators which need improvement to craft regional strategies. This framework is of added value for policymakers to customize their support programmes so that specific producers can enhance their competitive strategies. It could also be deployed in teaching programmes as a tool to address the importance of aligning different types of indicators to achieve better performance in the wine industry.
Keywords: 330; regional competitiveness; performance indicator; wine industry; competitiveness framework; systematic literature review